Phase Diagrams of Blends of Poly(phenylene ether), Polystyrene, and Diglycidyl Ether of Bisphenol A: Influence of the Molar Mass of Poly(phenylene ether) - Soulé, Ezequiel Rodolfo (2006)
Phase diagrams of ternary blends of poly(phenylene ether) (PPE, M n = 1.2 and 12 kg mol-1), polystyrene (PS, Mn = 22.5 kg mol-1), and diglycidyl ether of bisphenol A (DGEBA) were experimentally obtained in an extended range of temperatures and fitted with the Flory-Huggins model using three binary interaction parameters. A significant increase in miscibility together with the appearance of an immiscibility loop was found for PPEs with Mn values comprised in the range between 1 and 10 kg mol-1. This enables us to obtain initial homogeneous solutions in regions of high DGEBA concentrations, a possibility that was not previously reported for this ternary blend. This opens new possibilities for the toughening of epoxies replacing a single thermoplastic with a thermoplastic blend where both components (PS and PPE) are completely miscible.